Supporting family carers of children and adults with intellectual disability. (September 2020) - Kelly, Caraíosa; Craig, Sarah; McConkey, Roy
Summary: The extra strains experienced by families who care for a relative with intellectual disabilities are well documented. The provision of overnight (respite) breaks or supports in the home are common ways of supporting family carers. Often demand exceeds supply. Using data from a national register in Ireland, child and adults who received overnight breaks and in-home support were identified along with the characteristics that distinguished them from families that did not have these services. Moreover, changes in provision over a 10-year period were monitored and variations in provision across the country were ascertained. Findings: Overnight breaks were the dominant form of family support in Ireland. However, they were available to fewer persons in 2017 compared to 2007, whereas the provision of home supports remained constant. Persons with severe and profound disabilities were those most likely to receive home supports or overnight breaks as were persons aged 30 years and over. There were persistent marked differences across the country in the provision of home supports, although the variation in the usage of overnight breaks had contracted somewhat in 2017. Applications: Additional investment is needed to provide supports for families, given the increasing numbers of persons with intellectual disabilities living at home. A wider range of support options would provide greater choice and arguably improve the cost-effectiveness of current resources. Frontline professionals, such as social workers, need to be to the fore in persuading service commissioners of these needs based on empirical data as well as their personal experiences.